Modelling economic effects of reducing non-tariff measures in the food processing sector of malaysia using computable general equilibrium - Yew V.S.-H.; Al-Amin A.Q.; Devadason E.S. (Malaysian Economic Association, 2023)
The import intensive food processing sector in Malaysia is highly regulated with non-tariff measures (NTMs) from the import side. However, the ad-valorem equivalents (AVEs) of those NTMs vary substantially across the subsectors of food processing. To assess the trade costs or plausible protection effects associated with NTMs, the computable general equilibrium (CGE) model is employed with partial removal of NTMs from the baseline scenario with NTMs. The disaggregated impact of a reduction in NTMs indicate disproportionate gains in trade (both imports and exports) across the various subsectors, with highest gains derived by the subsectors with relatively high AVEs, namely dairy products, bakery products and animal feeds. The simulation findings further show that the overall impact of a reduction in NTMs on trade is larger in the long run relative to the short run, suggesting slow responses to such policy changes, as NTMs present themselves as a package and not as an instrument. 2020 Malaysian Economic Association. All rights reserved.